Morphological and molecular systematics of the genus Miscanthus anderss - Scally, Louise (Trinity College (Dublin, Ireland). Department of Botany, 2001)
Increasing fuel costs and a depletion of the earth's natural energy resources have lead to a global search for alternative sources of renewable energy. In response, the "European Miscanthus network" funded by the European Agro-Industrial Research programme (AIR) of the European Union’s Directorate General (DG) VI was established. The aim of this network was to establish the potential of certain species and cultivars of the genus Miscanthus as a potential source of renewable biomass for energy and fibre. During the initial stages of this research it became clear that the classification of the genus Miscanthus was confusing and that it was necessary to establish a reliable classification system and a method of identifying individual accessions of the genus.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin